Integrated Carbon Nanotube/MoO3 Core/Shell Arrays as Freestanding Air Cathodes for Flexible Li–CO2 Batteries. Issue 10 (31st August 2021) - Chen, Minghua; Liu, Yue; Liang, Xinqi; Wang, Fan; Li, Yu; Chen, Qingguo
Abstract : Li–CO2 batteries are a hopeful candidate for electrochemical energy storage applications by converting the greenhouse gas CO2 to chemicals. However, the energy harvest ability and cycling stability of powder catalysts have greatly restricted the practical application of this technique. Herein, chemical vapor deposition (CVD) and atomic layer deposition (ALD) methods are used to produce MoO3 ‐coated carbon nanotube (MoO3 @CNT) arrays as cathode catalyst materials for Li–CO2 batteries. The interwoven structure of CNTs provides substantial electron transport pathways and the high uniformity of deposition enhances the catalytic activity/stability of the whole electrode, effectively promoting the diffusion of CO2 during the discharge process and accelerating the decomposition of Li2 CO3 under low charge overpotential. At a current density of 0.05 mA cm −2 and a fixed capacity of 1 mAh cm −2, the as‐prepared electrode presents a competitively low charging overpotential (1 V), an impressive lifetime (300 cycles) and ultrahigh total discharge capacity (30.25 mAh cm −2 ). Using the pouch Li‐CO2 battery packed with the prepared electrode as the power supply, commercial light emitting diode equipment can be stably lit up under different bending angles. The research results promote the application of Li–CO2 batteries in portable systems. Abstract : Carbon nanotube (CNT)/MoO3 integrated arrays are obtained through controllable and scalable methods. Benefiting from the integrated electrode design and the synergistic effect between MoO3 and CNTs and the integrated electrode design, the CNT/MoO3 cathode has superior electrochemistry performance and excellent mechanical stability.